2018
DOI: 10.1038/s41467-018-06951-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustained activation of the Aryl hydrocarbon Receptor transcription factor promotes resistance to BRAF-inhibitors in melanoma

Abstract: BRAF inhibitors target the BRAF-V600E/K mutated kinase, the driver mutation found in 50% of cutaneous melanoma. They give unprecedented anti-tumor responses but acquisition of resistance ultimately limits their clinical benefit. The master regulators driving the expression of resistance-genes remain poorly understood. Here, we demonstrate that the Aryl hydrocarbon Receptor (AhR) transcription factor is constitutively activated in a subset of melanoma cells, promoting the dedifferentiation of melanoma cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(103 citation statements)
references
References 61 publications
8
88
1
Order By: Relevance
“…Mechanisms of resistance were fasten on MAPK (mitogen‐activated protein kinase) pathway reactivation, gene expression change including acquired overexpression of upstream NRSA and MEK mutations, amplification or alternate splicing of mutant BRAF, reactivation and autophagy of ERK (extracellular regulated protein kinases), COT and MLKs overexpression . Besides, tumor microenvironment change such as microRNA and aryl hydrocarbon receptor (AhR) transcription factor has been found in BRAF resistance . Immune microenvironment change such as increasing PD1+ melanoma cells was also related to tumor recurrence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of resistance were fasten on MAPK (mitogen‐activated protein kinase) pathway reactivation, gene expression change including acquired overexpression of upstream NRSA and MEK mutations, amplification or alternate splicing of mutant BRAF, reactivation and autophagy of ERK (extracellular regulated protein kinases), COT and MLKs overexpression . Besides, tumor microenvironment change such as microRNA and aryl hydrocarbon receptor (AhR) transcription factor has been found in BRAF resistance . Immune microenvironment change such as increasing PD1+ melanoma cells was also related to tumor recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…26 Besides, tumor microenvironment change such as microRNA and aryl hydrocarbon receptor (AhR) transcription factor has been found in BRAF resistance. 27,28 Immune microenvironment change such as increasing PD1+ melanoma cells was also related to tumor recurrence. 29 These findings suggested that the occurrence of acquired resistance could be prevented or delayed in combination therapy, which included downstream target inhibition and BRAF inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…We selected the 501Mel cell line since i) these cells display a melanocytic differentiation state as the majority of diagnosticated melanoma, ii) they harbor the BRAF(V600E) mutation as ~50% of cutaneous melanoma, iii) they are highly sensitive to BRAFi with an IC50 value of 0.45 µM to vemurafenib [PLX4032] 18,28 and importantly iv) they are unable to generate tumor in immunodeficient mice 29 . This latter characteristic may allow to identify tumor-promoting genes.…”
Section: Identification Of Tumor-promoting Genes By In Vivo Gain-of-fmentioning
confidence: 99%
“…Such alterations may also occur de novo, during treatment 12 . In addition, there is increased evidence that nongenetic reprogramming may confer drug tolerant and/or resistant phenotypes to melanoma cells 6,[16][17][18][19][20] . Earlier works demonstrated that phenotype switching from a proliferative to an invasive/mesenchymal-like state is also likely to contribute to therapy resistance [21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…An anti-leprosy Food and Drug Administration (FDA)-approved drug and AhR antagonist clofazimine suppressed multiple myeloma in transgenic mice [8]. Targeting of AhR with antagonists was suggested as a strategy for delaying the relapse during the treatment of melanoma with vemurafenib [9] or for inhibiting constitutive AhR activity in prostate cancer [10]. The use of AhR ligands is not limited to anti-cancer therapy but given the roles of AhR in the intestines and skin, targeting the AhR is challenging also in the treatment of inflammatory bowel disease (IBD) or skin pathologies.…”
Section: Introductionmentioning
confidence: 99%